2006
DOI: 10.1093/intimm/dxl057
|View full text |Cite
|
Sign up to set email alerts
|

Gld mutation of Fas ligand increases the frequency and up-regulates cell survival genes in CD25+CD4+ TR cells

Abstract: The Fas pathway and regulatory T (T(R)) cells play intertwining roles in controlling T cell tolerance through deletion and suppression of autoreactive T cells. Impairment of either mechanism causes severe T cell lymphoproliferation albeit with opposing outcomes. T cell lymphoproliferation induced by defective Fas pathway does not cause overt lymphocytic infiltration but rather prevents an important set of T cell-mediated autoimmune diseases. In contrast, deficiency in T(R) cell causes fulminant autoimmunity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 56 publications
4
60
1
Order By: Relevance
“…We found that Treg cells derived from both young and old lpr/lpr gld/gld mice ably suppress T cell proliferation in vitro. These data are consistent with other studies that have shown that blocking with an anti-FasL antibody has no effect on Treg cell suppression [39,40], and that Treg cells from gld/gld mice can inhibit gld/gld Th cell proliferation [11]. Conversely, we found that Treg cells suppress the proliferation of Th cells derived from either young or old lpr/lpr gld/gld mice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that Treg cells derived from both young and old lpr/lpr gld/gld mice ably suppress T cell proliferation in vitro. These data are consistent with other studies that have shown that blocking with an anti-FasL antibody has no effect on Treg cell suppression [39,40], and that Treg cells from gld/gld mice can inhibit gld/gld Th cell proliferation [11]. Conversely, we found that Treg cells suppress the proliferation of Th cells derived from either young or old lpr/lpr gld/gld mice.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, in some murine models of SLE Treg cells are diminished and/or have reduced Foxp3 protein expression [8][9][10]. In contrast, 16-20 week old C3H gld/gld mice have an increased frequency of Foxp3 + T cells with Foxp3 protein expressed at levels similar to normal mice [11]. The functional capacity of Treg cells to block T cell proliferation in vitro also varies according to strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty nanograms of cDNA of each sample was used for each real-time PCR reaction using gene-specific primer and probe sets in the Quant Studio 12 K Flex real-time PCR system. Realtime data were normalized with b-actin and analyzed as previously described 31 and fold change in mRNA expression was calculated using the 2-ΔΔCT method.…”
Section: Adoptive Transfer and Assessment Of Kidney Injurymentioning
confidence: 99%
“…Although gld mice display elevated Treg numbers, the latter was unaltered in lpr mice (12,13). Moreover, several in vivo studies demonstrated that Treg numbers decline during an immune response as a result of CD95 ligation, whereas others claimed that CD95L expression by Tregs induces responder cell death in vitro (14)(15)(16)(17).…”
Section: Foxp3mentioning
confidence: 99%